Council Transcripts - Dauti, Marsela (Uppsala University, 2020)
Project title: Gender Quotas and the Democratic Quality of Local Decision-Making Processes in Clientelistic Regimes  Project Acronym: GenderQuotas

Country: Albania

The text file titled “Council Transcripts 2016” refers to the transcripts of council meetings held during August - December 2016.

The text file “Council Transcripts 2018” refers to the transcripts of council meetings held during August - December 2018. The study was conducted in the councils of Durrës, Fier, Korçë, Kukës, Librazhd, Malësi e Madhe, Mat, Pukë, Sarandë, Tiranë, Ura Vajgurore.

Language: Albanian

Organization supporting fieldwork: Women’s Network Equality in Decision-Making (http://www.platformagjinore.al/)

The first wave of data collection (August - December 2016) was funded by United Nations Development Programme – Albania, contract number ALB-092-2016. The second round of data collection (August - December 2018) was funded by the European Union’s Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No 792969.

The dataset was originally published in DiVA and moved to SND in 2024.

Transkriberingar av fullmäktigemöten i Albanien.

Textfilen med titeln "Council Transcripts 2016" avser utskrifterna av fullmäktiges sammanträden under augusti - december 2016.

Textfilen "Council Transcripts 2018" avser utskrifter av fullmäktigemöten som hölls under augusti - december 2018. Studien genomfördes i fullmäktigeförsamlingarna i Durrës, Fier, Korçë, Kukës, Librazhd, Malësi e Madhe, Mat, Pukë, Sarandë, Tiranë, Ura Vajgurore.

Språk: Albanska


Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Council Transcripts
Keywords: council meetings; council meetings; democratization; democratization; Gender quotas; Gender quotas; Political Science; Political Science; political representation; political representation; Political Science; Statsvetenskap